2007
DOI: 10.1073/pnas.0706987104
|View full text |Cite
|
Sign up to set email alerts
|

Blood gene expression signatures predict exposure levels

Abstract: To respond to potential adverse exposures properly, health care providers need accurate indicators of exposure levels. The indicators are particularly important in the case of acetaminophen (APAP) intoxication, the leading cause of liver failure in the U.S. We hypothesized that gene expression patterns derived from blood cells would provide useful indicators of acute exposure levels. To test this hypothesis, we used a blood gene expression data set from rats exposed to APAP to train classifiers in two predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 21 publications
8
101
0
1
Order By: Relevance
“…20 A more global picture of the impacted biology can be achieved by gene expression studies, and various exposures have been shown to alter gene expression profiles in blood. [21][22][23] Indeed, several studies have shown that gene expression in blood can distinguish between average subject populations, such as those with early stage non-small cell lung cancer, from those with non-malignant lung disease, 24,25 subjects with chronic obstructive pulmonary disease (COPD) from healthy smokers, 26 and even smokers with no detectable disease from nonsmokers. [27][28][29][30][31][32][33] A transcriptome-based exposure response signature could be as simple as the presence or absence of a single gene expression, or, more likely, could be characterized by the expression levels of a collection of genes, each contributing to a specific diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…20 A more global picture of the impacted biology can be achieved by gene expression studies, and various exposures have been shown to alter gene expression profiles in blood. [21][22][23] Indeed, several studies have shown that gene expression in blood can distinguish between average subject populations, such as those with early stage non-small cell lung cancer, from those with non-malignant lung disease, 24,25 subjects with chronic obstructive pulmonary disease (COPD) from healthy smokers, 26 and even smokers with no detectable disease from nonsmokers. [27][28][29][30][31][32][33] A transcriptome-based exposure response signature could be as simple as the presence or absence of a single gene expression, or, more likely, could be characterized by the expression levels of a collection of genes, each contributing to a specific diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because of their clinical accessibility, circulating blood cells are very useful for assessing disease-related changes in gene expression. Bushel et al have shown that gene expression data from PBMCs can predict environmental exposure levels (Bushel et al, 2007). Because most diseases, including cancers, result from interactions between genetic and environmental factors, gene expression data for PBMCs can be used as biomarkers for the early detection of diseases and for the identification of clinicopathological features and estimation of prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression can provide information that refl ects the physiological status of the body. Bushel et al (27) confi rmed the hypothesis that gene expression patterns derived from peripheral blood cells could predict the degree of liver injury following an acute overdose of paracetamol before it can be detected by traditional parameters. Analysis of the genes revealed more alteration in the infl ammatory pathways involving IL-1 and NF-kB.…”
Section: Introductionmentioning
confidence: 88%